Formation of military-professional competencies with the use of problem-situational tasks - Elena G. Porshneva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article covers application of active educational methods at Military Training Faculty of a civil university, it being element of stepping-up of educational activity through simulation of real situations aimed to form professional military competence: ability to identify typical failures that occur in operation of diesel power plants; ability to eliminate failures. Active involvement of students into educational activities boosts quality of training at Military Department, for this reason problem situational tasks for technical military course «Construction, operating principle, operation and application of diesel power plants» have been developed to search for solutions in a specific practical situation that arise in diesel power station operation. While analyzing received task, students used real military equipment in practical trainings aimed at active development of professional military competence. Problem situational tasks contribute to deeper study of technical military subjects, development of abilities to solve problems, creative thinking, independent work and reflexive skills of students.In work an experiment was set up to verify hypothesis based on assumption that level of preparation of students at Military Department can be improved through development and implementation of technical military discipline based on integrated use of modern methods and means of education. Results were compared on the basis of Pearson’s statistical criterion  2 . Experiment results prompted conclusion on effectiveness of developed technical military discipline as in similar and even slightly worse initial conditions, students of experimental group trained in accordance with developed academic discipline with application of active methods and teaching aids, at course end show higher results compared to control group students, who were trained with traditional methods.Thus, study of disciplines of technical military education at Military Department of Aerospace Force of Military Training Faculty in a civil university with application of problem situational tasks is aimed at development of professional military competences and personal traits and achievement of main goal of training at Military Training Faculty - readiness of graduates for professional activity in accordance with competence requirements for relevant military occupational specialty.